REDUCING ENGLISH SPEAKING ANXIETY IN CLASSROOM PRESENTATIONS: THE ROLE OF CHATBOT-ASSISTED PREPARATION - Muhammad Fathur Rahman Khalik (ELP (Journal of English Language Pedagogy), 2025)
Speaking anxiety is a common issue among students in an English learning context, particularly when engaging in oral presentations. This study investigates whether chatbot-assisted preparation can reduce speaking anxiety among non-English major students. Employing pre-test post-test control group design, 40 participants were randomly distributed to either an experimental group (preparation with chatbot assistance) or a control group (preparation without chatbot assistance). A modified, Indonesian-translated version of the Foreign Language Classroom Anxiety Scale (FLCAS) was used to measure anxiety levels. Independent pre-test comparisons showed no significant difference between groups (p = 0.635), indicating baseline equivalence. Paired-sample t-test results revealed a significant decrease in anxiety within the experimental group (p < 0.001), while the control group showed no significant change (p = 0.558). Finally, independent post-test comparisons indicated a significantly lower anxiety level in the experimental group compared to the control group (p = 0.002). These findings suggest that chatbots can be a valuable tool for reducing speaking anxiety and enhancing oral performance in foreign language education.